Melatih Kemandirian Anak dengan Kegiatan Fun Cooking Selama BDR: Training Children's Independence with Fun Cooking Activities During BDR - Farantika, Dessy (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2021)
Abstract The implementation of BDR activities significantly changes the learning process. Significant changes can be seen from the implementation that was initially carried out in the classroom with the teacher changing to the implementation of learning at home with parental assistance. In the implementation of learning, teachers and parents are required to design interesting, memorable and meaningful lessons so that the implementation is fun and not boring. In choosing learning activities, you must also pay attention to the learning objectives so that children can still achieve their learning outcomes. Some schools choose to create meaningful activities by doing daily activities that are fun with parents and do not lose the essence of meaningful learning. This is because children can learn through direct experience and activities. During BDR activities, children spend time with their parents at home to learn and do activities together. This is the right opportunity to teach a variety of things not only academically but also life skills that need to be trained. One of the activities that can develop all aspects of development and life skills, especially meaningful independence that can be done with parents, is fun cooking. Fun cooking is an activity that is very beneficial for children, because fun cooking can develop all aspects of child development. Funcooking activities are activities where children can try directly to make food from raw materials until it becomes ripe through the processes and guidance of teachers / parents. Besides being able to develop all aspects of development, Fun Cooking can develop children's independence. Through fun cooking activities, children are directly involved in it, starting from choosing recipes to cleaning up used utensils. This is where the role of parents to train and teach children about independence in carrying out fun cooking activities that are fun and meaningful in children's learning activities. Independence is an attitude that is obtained cumulatively through the process that a person experiences in his development, where in the process of being independent, individuals learn to deal with various situations in their social environment until they are able to think and take appropriate action in overcoming each situation. The independence of children can be stimulated by consistent daily activities. Independence also needs to be trained and used since childhood.